A Critical Genealogy of Rulership, Abuse, and Institutional Counterbalance in the Islamic Caliphates - Anam, A'azliansyah Farizil; Biçer, Beytullah (An-Nur International Journal of Islamic Thought, 2025)
This article challenges conventional debates on Islam and human rights, often focusing on doctrinal compatibility. It argues that a more robust and universal human rights framework must be grounded not in idealized historical traditions, but in a pragmatic acknowledgment of the historical reality of state-sponsored abuse. Employing a critical-historical and genealogical method, this study analyzes primary Islamic sources—including historical chronicles and legal treatises—to reconstruct the political history of governance, dissent, and violence from the pre-Islamic period through the classical caliphates. The findings reveal a profound dissonance between the theoretical ideal of the "just ruler" and the statistical reality, in which over 94% of caliphs and sultans were unjust by the tradition's standards. This history of abuse, however, paradoxically fostered the emergence of crucial institutional counterbalances, most notably an independent scholarly class (ʿUlamāʾ) that served as a moral and legal check on executive power. This study concludes that the most vital lesson from Islamic political history is the necessity of empowering such durable checks on power, shifting the focus from creating a perfect government to constraining the inevitable transgressions of an imperfect one.